The Use of Taking Notes on Report Text - Nila Susanti (JETLe (Journal of English Language Teaching and Learning), 2020)
Some problems of reading and writing incompetency are suffered by students commonly. It can become more difficult for them to understand what they are reading and writing. Additionally, it can become difficult to gain a deeper accepting of the text, something that requires assimilating competency, experience, and knowledge. This paper attempts to describe the use of taking notes on report text. Taking notes could help secondary level students to simplify the process of reading and writing report text. Students or learner who has decent skill of reading and writing and theory of taking notes will find less difficulties to write down report text as teacher requires. Therefore, teacher should equipped students by academic writing skill particularly about taking notes. Reading a lot and keep on writing are the best way to achieve those abilities.Keywords: reading, writing, taking notes, report text.